Car anti-smog screen

By adopting three-layer structure anti-haze window screens, combined with electrospinning method and ultrasonic welding technology, multiple dust accumulation bags are formed, which solves the problem that existing automotive screen windows cannot effectively block haze and dust accumulation, and achieves higher filtration effect and longer service life.

CN111605386BActive Publication Date: 2025-04-18JUNADA (QINGDAO) TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201910133368.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-02-22
Publication Date
2025-04-18
Estimated Expiration
2039-02-22

AI Technical Summary

Technical Problem

Existing automotive screens cannot effectively block air pollutants such as haze into the vehicle, and during use, it is easy to affect the filtration effect and service life due to dust accumulation.

Method used

The anti-smog window screen with a three-layer structure, including metal wire mesh, electrospun nanofiber membrane and plastic protection mesh, is formed through electrospinning and ultrasonic welding technology, to improve the filtering capacity and dust accumulation capacity of the screen window.

Benefits of technology

Effectively block air pollutants such as haze, reduce the number of cleanings, extend the service life, improve the convenience of use, and maintain ventilation and lighting effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111605386B_ABST
    Figure CN111605386B_ABST
Patent Text Reader

Abstract

The present invention discloses a vehicle anti-smog screen window, comprising a screen window frame adapted to a vehicle window frame and an anti-smog window screen installed in the screen window frame, the screen window frame is provided with a connecting component for connecting the vehicle window frame, the anti-smog window screen is a three-layer structure, which is sequentially provided as a metal wire mesh, an electrospun nanofiber film and a plastic protective net, the electrospun nanofiber film is directly sprayed and composited on the metal wire mesh by an electrostatic spinning method, the plastic protective net is fixed on the electrospun nanofiber film by ultrasonic welding, the welding lines of the ultrasonic welding are multiple and staggered on the anti-smog window screen, and the plastic protective net is fixed to the electrospun nanofiber film by welding lines to form multiple dust bags. The screen window can block air pollutants such as haze from entering the vehicle, and has a high dust accumulation tolerance, can reduce the number of cleaning times required for use, prolong the service life, and is more convenient to use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of vehicle screen windows, and in particular relates to a vehicle anti-smog screen window. Background Art

[0002] With the popularization of household cars, the auto parts market has begun to show vitality. At present, car screens that can prevent mosquitoes from flying into the car are available on the market. In recent years, haze, dust or sandstorms have occurred frequently, and the impact of air pollution on health has gradually attracted people's attention. Most of the existing car screens cannot prevent haze and other air pollutants from entering the car, and can no longer open windows for ventilation while ensuring clean air in the car.

[0003] In order to make the car screen have the function of blocking air pollutants, Chinese patent CN206562902U discloses a magnetic car anti-smog screen, whose window screen body includes window screen cloth, electrostatic electret filter and activated carbon mesh cloth. The filter layer formed by sewing the edges of the window screen cloth, electrostatic electret filter and activated carbon mesh cloth together can filter some air pollutants. However, the multi-layer filter layer (or filter body) connected by sewing the edges filters the smog. Since the use state of the car screen is basically vertical installation, the dust filtered by each filter layer will be accumulated in the lower part of the gap between the filter layers under the action of gravity, which is very easy to block the air flow channel at the lower part of the filter layer, affecting the filtering effect and the service life of the filter layer. The filter layer needs to be frequently replaced or cleaned, which is very inconvenient to use. Summary of the invention

[0004] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide an anti-smog screen window for a vehicle, which can block air pollutants such as smog from entering the vehicle and has a high ability to withstand dust accumulation, thereby reducing the number of cleaning times required for use, extending the service life, and making it more convenient to use.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A vehicle anti-smog screen window comprises a screen window frame adapted to a vehicle window frame and an anti-smog window screen installed in the screen window frame, the screen window frame is provided with a connecting component for connecting to the vehicle window frame, the anti-smog window screen is a three-layer structure, which is sequentially arranged as a metal wire mesh, an electrospun nanofiber membrane and a plastic protective net, the electrospun nanofiber membrane is directly sprayed and composited on the metal wire mesh by an electrostatic spinning method, the plastic protective net is fixed to the electrospun nanofiber membrane by ultrasonic welding, there are multiple welding lines of the ultrasonic welding and they are staggered on the anti-smog window screen, and the plastic protective net is fixed to the electrospun nanofiber membrane by welding lines to form a plurality of dust bags.

[0007] Preferably, the dust bags are all rhombus-shaped with equal size, and the dust bags are evenly arranged on the anti-smog window screen.

[0008] Preferably, the metal wire mesh is a copper-plated stainless steel mesh, and the plastic protective mesh is a silver-plated nylon mesh.

[0009] Preferably, the mesh number of the metal wire mesh is 80-150 meshes, the mesh number of the plastic protection mesh is 40-70 meshes, the porosity of the electrospun nanofiber membrane is greater than 80%, and the average pore size is 300-500 nm.

[0010] Preferably, the connecting component is a magnet block attached to the screen window frame, and the number of the magnet blocks is multiple.

[0011] Preferably, the screen window frame is covered with a cloth edging, and the magnet block is arranged inside the cloth edging.

[0012] Preferably, the screen window frame is provided with a plurality of openings which can be used for folding the screen window frame.

[0013] Preferably, the number of the openings is four, two of which are arranged along a vertical line passing through the midpoint of the bottom edge of the screen window frame, and the other two openings are arranged along a horizontal line passing through the midpoint of any side edge of the screen window frame.

[0014] Preferably, the screen window frame is provided with elastic buckles connecting the screen window frames on both sides of the opening, and the elastic buckles are arranged in a one-to-one correspondence with the opening.

[0015] Preferably, the electrospun nanofiber membrane is a cordierite nanoparticle / hydrophobic and oleophobic polymer composite nanofiber membrane, the content of cordierite nanoparticles in the electrospun nanofiber membrane is 1-4 wt %. The preparation method of the electrospun nanofiber membrane comprises the following steps:

[0016] Preparing a spinning precursor solution: dispersing the cordierite nanoparticles in an organic solvent that can dissolve the hydrophobic and oleophobic polymer material to prepare a dispersion solution, adding the hydrophobic and oleophobic polymer material to the dispersion solution and mixing evenly to obtain a clear solution, which is a precursor spinning solution;

[0017] Electrospinning membrane: Add the prepared precursor spinning solution into the liquid storage mechanism of the electrospinning equipment, use the metal wire mesh as the spinning collection mechanism of the electrospinning equipment, adjust the spinning parameters, and use the electrospinning equipment to directly electrospin the electrospun nanofiber membrane on the upper surface of the metal wire mesh.

[0018] Preferably, the electrospun nanofiber membrane is a cordierite nanoparticle / thermoplastic polyurethane composite nanofiber membrane;

[0019] The step of preparing the spinning precursor solution is as follows: dispersing the cordierite nanoparticles in an organic solvent obtained by mixing N,N-dimethylformamide and tetrahydrofuran, treating with an ultrasonic crusher for 40-60 minutes to uniformly disperse the cordierite nanoparticles in the organic solvent to prepare a dispersion solution, wherein the volume ratio of N,N-dimethylformamide to tetrahydrofuran in the organic solvent is 1:1, adding the thermoplastic polyurethane particles to the dispersion solution, heating in a water bath at 40° C. and stirring for 4-6 hours to obtain a clear solution, which is the precursor spinning solution; the content of the thermoplastic polyurethane particles in the spinning precursor solution is 20-25wt%, and the percentage of the cordierite nanoparticles to the total mass of the cordierite nanoparticles and the thermoplastic polyurethane particles is 1-4wt%;

[0020] The spinning parameters in the electrospinning membrane making step are: spinning distance 15-25 cm, spinning voltage 45-60 kV, spinning temperature 25-30° C., humidity 20-40% RH, and spinning time 10-15 min.

[0021] Preferably, the method for preparing the cordierite nanoparticles comprises the following steps:

[0022] Sol preparation: According to cordierite 2MgO·2Al 2 O 3 5SiO 2 The stoichiometric ratio of ingredients was weighed, and Mg(NO 3 ) 2 6H 2 O and Al(NO 3 ) 3 9H 2 O is dissolved in anhydrous ethanol, heated and stirred until completely dissolved, and after cooling, a mixed solution of ethyl orthosilicate and anhydrous ethanol is slowly dripped in, wherein the volume ratio of ethyl orthosilicate to anhydrous ethanol in the mixed solution is 1:2, the obtained mixture is heated to 52°C and stirred under reflux, the pH is adjusted to 2.5 with nitric acid, and stirred for reaction for 3 hours to form a sol;

[0023] Gel preparation: Place the obtained sol in a 60°C water bath and let stand for 48 hours to form a gel;

[0024] Sintering: The obtained gel is placed in a ceramic container, heated at 500°C for 10 hours, and then the obtained product is sintered at 1250°C for 2 hours to obtain cordierite powder;

[0025] Crushing: The obtained cordierite powder is crushed by ball milling to obtain cordierite nanoparticles, wherein the average particle size of the cordierite nanoparticles is 200 to 500 nm.

[0026] Compared with the prior art, the advantages and positive effects of the present invention are: providing a vehicle anti-smog screen window, which can block air pollutants such as smog from entering the vehicle, has a high dust tolerance, can reduce the number of cleaning times required, prolongs the service life, and is more convenient to use. Specifically:

[0027] (1) The plastic protective net of the vehicle anti-smog screen window of the present application is fixed to the electrospun nanofiber membrane through welding lines to form multiple dust bags, so that the haze particles filtered by the electrospun nanofiber membrane can be stored in the dust bags distributed on the entire anti-smog window screen. Compared with the conventional filter window, the dust is concentrated in the lower part of the filter body. It can withstand a larger amount of dust accumulation while ensuring the ventilation and filtering effect, thereby reducing the number of cleaning times required for normal use of the window screen, extending the service life of the filter body, and making it more convenient to use.

[0028] (2) The main filter element of the anti-smog screen for vehicles of the present application is an electrospun nanofiber membrane made by an electrospinning method, which has unique physical and chemical properties such as large specific surface area and high porosity. It can prevent the passage of PM2.5 haze particles through pore screening without affecting the flow of gas molecules. Compared with traditional filters, the electrospun nanofiber membrane has a small thickness and a large porosity, which can ensure air permeability and light transmittance, and can ensure ventilation and lighting in the vehicle when in use.

[0029] (3) The dense surface structure of the metal mesh of the anti-smog screen for vehicles of the present application can pre-filter the outdoor air, effectively blocking large suspended particles such as smoke and pollen from entering the dust bag. The metal mesh can also reflect ultraviolet rays, which can improve the radiation protection function of the anti-smog window screen. At the same time, the plastic protective layer composited on the surface of the electrospun nanofiber membrane by ultrasonic welding can not only form a dust bag with the electrospun nanofiber membrane to increase the dust carrying capacity of the anti-smog window screen, but also protect the electrospun nanofiber membrane to extend the service life of the product.

[0030] (4) The electrospun nanofiber membrane that plays a filtering role in the anti-smog screen for vehicles of the present application preferably adopts a cordierite nanoparticle / hydrophobic and oleophobic polymer material composite nanofiber membrane. The cordierite nanoparticles contained therein have high thermal conductivity and infrared emissivity, which can increase the heat dissipation area and conductivity of the electrospun nanofiber membrane, thereby significantly improving the effect of heat exchange, and can quickly dissipate the heat in the car, which can have the effect of reducing the temperature inside the car in hot summer. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a structural schematic diagram of the anti-smog screen window for vehicles of the present invention;

[0032] Figure 2 It is a structural schematic diagram of the vehicle anti-smog screen window of the present invention with the elastic buckle removed;

[0033] Figure 3 For Figure 2 A magnified view of part A;

[0034] Figure 4 is a cross-sectional view of the anti-haze window screen of the present invention;

[0035] Figure 5 It is a schematic structural diagram of the anti-smog screen window for vehicles with hemming of the present invention;

[0036] Figure 6 is a SEM image of the electrospun nanofiber membrane of Example 2;

[0037] Figure 7 is a SEM image of the cordierite nanoparticles of Example 1;

[0038] In the above figure: 1-screen window frame, 11-magnet block, 12-opening, 13-elastic buckle, 14-cloth edging, 2-anti-smog window screen, 21-dust bag, 22-welding line, 23-metal wire mesh, 24-electrospun nanofiber membrane, 25-plastic protective net. DETAILED DESCRIPTION

[0039] The present invention is described in detail below by way of exemplary embodiments. However, it should be understood that elements, structures, and features in one embodiment may also be beneficially combined in other embodiments without further description.

[0040] It should be noted that, in the description of the present invention, the directions or positional relationships indicated by terms such as “inside”, “outside”, “up”, “down”, “left”, “right”, “front” and “back” are based on the positional relationships shown in the accompanying drawings and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention.

[0041] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features.

[0042] Embodiment 1:

[0043] like Figure 1-4As shown, a vehicle anti-smog screen window comprises a screen window frame 1 adapted to a vehicle window frame and an anti-smog window screen 2 installed in the screen window frame 1, the screen window frame 1 is provided with a connecting component for connecting to the vehicle window frame, the anti-smog window screen 2 is a three-layer structure, which is sequentially arranged as a metal wire mesh 23, an electrospun nanofiber membrane 25 and a plastic protective net 25, the electrospun nanofiber membrane 24 is directly sprayed and compounded on the metal wire mesh 23 by an electrostatic spinning method, the plastic protective net 25 is fixed on the electrospun nanofiber membrane 24 by ultrasonic welding, the ultrasonic welding welding lines 22 are multiple and staggered on the anti-smog window screen 2, and the plastic protective net 25 is fixed to the electrospun nanofiber membrane 24 by the welding lines 22 to form a plurality of dust bags 21.

[0044] The above-mentioned anti-smog screen for vehicle mainly uses electrospun nanofiber membrane 24 to filter haze. Since the plastic protective net 25 is fixed to the electrospun nanofiber membrane 24 through welding lines 22 to form multiple dust bags 21, the dust filtered by the electrospun nanofiber membrane 24 can be stored in the dust bags 21 distributed on the entire anti-smog window screen 2, instead of all being accumulated in the lower part of the anti-smog window screen 2. Compared with the conventional filter window dust is concentrated in the lower part of the filter body, the anti-smog screen of this embodiment uses the entire anti-smog window screen 2 as the dust accumulation body, which can withstand a larger amount of dust accumulation while ensuring the ventilation and filtering effect, thereby reducing the number of cleaning times required for normal use of the window screen, extending the service life of the filter body, and being more convenient to use.

[0045] The electrospinning method used in this embodiment is a widely used method for preparing nanofiber membranes. The electrospun nanofiber membrane 24 can be directly sprayed and composited on the metal wire mesh 23 serving as the collecting electrode of the electrospinning device. The composite method is relatively simple. The electrospun nanofiber membrane 24 prepared by the electrospinning method has unique physical and chemical properties such as large specific surface area and high porosity. The average fiber diameter is in the micro-nano level. Each square centimeter of the nanofiber membrane is densely covered with micro-nano-scale micropores, which can prevent the passage of PM2.5 haze particles through pore size screening without affecting the flow of gas molecules. Compared with traditional filters, the electrospun nanofiber membrane 24 has a smaller thickness and a larger porosity, which can ensure air permeability and light transmittance, and can ensure ventilation and lighting in the vehicle when in use. The metal mesh 23 in the anti-smog window screen is not only a support for the electrospun nanofiber membrane 24 and a collector for preparing the electrospun nanofiber membrane 24, but also has a dense surface structure that can pre-filter outdoor air, effectively blocking large suspended particles such as smoke and pollen from entering the dust bag. The metal mesh 23 can also reflect ultraviolet rays, which can improve the radiation protection function of the anti-smog window screen 23. At the same time, the plastic protective layer composited on the surface of the electrospun nanofiber membrane 24 by ultrasonic welding can not only form a dust bag with the electrospun nanofiber membrane 24 to increase the dust tolerance of the anti-smog window screen 2, but also protect the electrospun nanofiber membrane 24 to extend the service life of the product.

[0046] Specifically, the dust bags 21 are all rhombuses of equal size, and the dust bags 21 are evenly arranged on the anti-haze window screen 2 .

[0047] Specifically, the metal wire mesh 23 is a copper-plated stainless steel mesh, and the plastic protection mesh 25 is a silver-plated nylon mesh. The metallic silver on the surface of the silver-plated nylon mesh can improve the antibacterial and radiation protection properties of the anti-smog window screen 2 and make the anti-smog window screen 2 more beautiful.

[0048] Specifically, the mesh number of the metal wire mesh is 80-150 meshes, the mesh number of the plastic protection mesh is 40-70 meshes, the porosity of the electrospun nanofiber membrane is greater than 80%, and the average pore size is 300-500 nm.

[0049] Specifically, the connecting component is a magnet block 11 attached to the screen window frame 1, and the magnet block 11 is provided in plurality. The above-mentioned anti-smog screen window for vehicle can be fixed on the window frame of the vehicle window made of metal material by adsorbing the magnet block, which is convenient for use and disassembly and cleaning.

[0050] Specifically, Figure 5 As shown, the screen window frame 1 is covered with a cloth edging 14 , and the magnet block 11 is arranged inside the cloth edging 14 .

[0051] Specifically, Figure 2-3As shown, the screen frame 1 is provided with a plurality of openings 12 that can be used to fold the screen frame 1. The arrangement of the openings 12 enables the above-mentioned anti-fog screen for vehicles to be folded along two openings 12 arranged in the same straight line, thereby reducing the space required for storage and facilitating use.

[0052] Specifically, there are four openings 12, two of which are arranged along a vertical line passing through the midpoint of the bottom edge of the screen window frame 1, and the other two openings 12 are arranged along a horizontal line passing through the midpoint of any side edge (such as the left side) of the screen window frame.

[0053] Specifically, the screen frame 1 is provided with elastic buckles 13 connecting the screen frames 1 at both sides of the opening 12, and the elastic buckles 13 are arranged one by one with the opening 12. The elastic buckles 13 provided on the screen frames 1 at both sides of the opening 12 can fix the relative positions of the screen frames 1 at both sides of the opening 12, ensuring the stability of the use state.

[0054] Specifically, the electrospun nanofiber membrane 24 is a cordierite nanoparticle / hydrophobic and oleophobic polymer composite nanofiber membrane, the content of cordierite nanoparticles in the electrospun nanofiber membrane 24 is 1-4 wt %. The preparation method of the electrospun nanofiber membrane 24 includes the following steps:

[0055] Preparing a spinning precursor solution: dispersing the cordierite nanoparticles in an organic solvent that can dissolve the hydrophobic and oleophobic polymer material to prepare a dispersion solution, adding the hydrophobic and oleophobic polymer material to the dispersion solution and mixing evenly to obtain a clear solution, which is a precursor spinning solution;

[0056] Electrospinning membrane: Add the prepared precursor spinning solution into the liquid storage mechanism of the electrospinning equipment, use the metal wire mesh 23 as the spinning collection mechanism of the electrospinning equipment, adjust the spinning parameters, and use the electrospinning equipment to directly electrospin the electrospun nanofiber membrane 24 on the upper surface of the metal wire mesh 23.

[0057] In the hot summer, as a relatively closed space, a car will generate a lot of heat when exposed to the sun, making the temperature inside the car much higher than the ambient temperature, seriously affecting the comfort of the ride. The traditional window opening for ventilation and the heat dissipation method of air convection heat conduction have a slow heat dissipation speed. The use of the above-mentioned anti-smog screen for vehicle can significantly improve the heat dissipation speed. The electrospun nanofiber membrane 24 that plays a filtering role in the above-mentioned anti-smog screen for vehicle preferably adopts cordierite nanoparticles / hydrophobic and oleophobic polymer composite nanofiber membrane. The cordierite nanoparticles contained therein have high thermal conductivity and infrared emissivity. The electrospun nanofiber membrane 24 directly blended with cordierite nanoparticles and hydrophobic and oleophobic polymer materials can form a macroscopically smooth and microscopically wavy radiation structure unit. Such a structure can increase the heat dissipation area and conductivity of the electrospun nanofiber membrane 24, so as to significantly improve the heat exchange effect, and can quickly dissipate the heat in the car, which can have the effect of reducing the temperature inside the car in the hot summer. In addition, the main material of the electrospun nanofiber membrane 24 is a hydrophobic and oleophobic polymer material, such as a polyurethane nanofiber membrane. The surface of the nanofiber membrane prepared from the hydrophobic and oleophobic polymer material has super-hydrophobic properties similar to the surface of a lotus leaf, and is highly effective and waterproof, making the anti-smog screen for the vehicle easy to clean and more convenient to use.

[0058] Specifically, the method for preparing the cordierite nanoparticles comprises the following steps:

[0059] Sol preparation: According to cordierite 2MgO·2Al 2 O 3 5SiO 2 The stoichiometric ratio of ingredients was weighed, and Mg(NO 3 ) 2 6H 2 O and Al(NO 3 ) 3 9H 2 O is dissolved in anhydrous ethanol, heated and stirred until completely dissolved, and after cooling, a mixed solution of ethyl orthosilicate and anhydrous ethanol is slowly dripped in, wherein the volume ratio of ethyl orthosilicate to anhydrous ethanol in the mixed solution is 1:2, the obtained mixture is heated to 52°C and stirred under reflux, the pH is adjusted to 2.5 with nitric acid, and stirred for reaction for 3 hours to form a sol;

[0060] Gel preparation: Place the obtained sol in a 60°C water bath and let stand for 48 hours to form a gel;

[0061] Sintering: The obtained gel is placed in a ceramic container, heated at 500°C for 10 hours, and then the obtained product is sintered at 1250°C for 2 hours to obtain cordierite powder;

[0062] Crushing: The obtained cordierite powder is ball-milled to obtain cordierite nanoparticles (morphology as Figure 7As shown), the average particle size of the cordierite nanoparticles is 200 to 500 nm.

[0063] Example 2

[0064] The electrospun nanofiber membrane 24 in Example 1 is a cordierite nanoparticle / thermoplastic polyurethane composite nanofiber membrane. The morphological characteristics of the electrospun nanofiber membrane are as follows: Figure 6 As shown;

[0065] The step of preparing the spinning precursor solution is as follows: dispersing the cordierite nanoparticles in an organic solvent obtained by mixing N,N-dimethylformamide and tetrahydrofuran, treating with an ultrasonic crusher for 40 minutes to uniformly disperse the cordierite nanoparticles in the organic solvent to prepare a dispersion solution, wherein the volume ratio of N,N-dimethylformamide to tetrahydrofuran in the organic solvent is 1:1, adding the thermoplastic polyurethane particles (TPU, Bayer 9370A, Germany) to the dispersion solution, heating and stirring in a water bath at 40° C. for 4 hours to obtain a clear solution, which is the precursor spinning solution; the content of the thermoplastic polyurethane particles in the spinning precursor solution is 20wt%, and the percentage of the cordierite nanoparticles to the total mass of the cordierite nanoparticles and the thermoplastic polyurethane particles is 1wt%;

[0066] The spinning parameters in the electrospinning membrane-making step are: spinning distance 15 cm, spinning voltage 45 kV, spinning temperature 25° C., humidity 20% RH, and spinning time 10 min.

[0067] Example 3

[0068] The electrospun nanofiber membrane 24 described in Example 1 is a cordierite nanoparticle / thermoplastic polyurethane composite nanofiber membrane;

[0069] The step of preparing the spinning precursor solution is as follows: dispersing the cordierite nanoparticles in an organic solvent obtained by mixing N,N-dimethylformamide and tetrahydrofuran, treating with an ultrasonic crusher for 50 minutes to uniformly disperse the cordierite nanoparticles in the organic solvent to prepare a dispersion solution, wherein the volume ratio of N,N-dimethylformamide to tetrahydrofuran in the organic solvent is 1:1, adding the thermoplastic polyurethane particles (TPU, Bayer 9370A, Germany) to the dispersion solution, heating and stirring in a water bath at 40° C. for 5 hours to obtain a clear solution, which is the precursor spinning solution; the content of the thermoplastic polyurethane particles in the spinning precursor solution is 22wt%, and the percentage of the cordierite nanoparticles to the total mass of the cordierite nanoparticles and the thermoplastic polyurethane particles is 2wt%;

[0070] The spinning parameters in the electrospinning membrane-making step are: spinning distance 20 cm, spinning voltage 52 kV, spinning temperature 27° C., humidity 30% RH, and spinning time 12 min.

[0071] Example 4

[0072] The electrospun nanofiber membrane 24 described in Example 1 is a cordierite nanoparticle / thermoplastic polyurethane composite nanofiber membrane;

[0073] The step of preparing the spinning precursor solution is as follows: dispersing the cordierite nanoparticles in an organic solvent obtained by mixing N,N-dimethylformamide and tetrahydrofuran, treating with an ultrasonic crusher for 60 minutes to uniformly disperse the cordierite nanoparticles in the organic solvent to prepare a dispersion solution, wherein the volume ratio of N,N-dimethylformamide to tetrahydrofuran in the organic solvent is 1:1, adding the thermoplastic polyurethane particles (TPU, Bayer 9370A, Germany) to the dispersion solution, heating and stirring in a water bath at 40° C. for 6 hours to obtain a clear solution, which is the precursor spinning solution; the content of the thermoplastic polyurethane particles in the spinning precursor solution is 25wt%, and the percentage of the cordierite nanoparticles to the total mass of the cordierite nanoparticles and the thermoplastic polyurethane particles is 4wt%;

[0074] The spinning parameters in the electrospinning membrane-making step are: spinning distance 25 cm, spinning voltage 60 kV, spinning temperature 30° C., humidity 40% RH, and spinning time 15 min.

[0075] Example 5

[0076] The structure of the anti-smog screen for vehicles of this embodiment is substantially the same as that of the first embodiment, except that the electrospun nanofiber membrane 24 of this embodiment is a hydrophobic and oleophobic polymer nanofiber membrane, such as a polyurethane nanofiber membrane.

[0077] Specifically, the electrospun nanofiber membrane 24 is a polyurethane nanofiber membrane, and the preparation method of the polyurethane nanofiber membrane includes the following steps:

[0078] Preparation of spinning precursor solution: adding thermoplastic polyurethane particles (TPU, Bayer 9370A, Germany) into an organic solvent, wherein the organic solvent is obtained by mixing N,N-dimethylformamide and tetrahydrofuran, wherein the volume ratio of N,N-dimethylformamide to tetrahydrofuran in the organic solvent is 1:1, heating in a water bath at 40°C and stirring for 4 hours to obtain a clear solution, which is the precursor spinning solution; the content of the thermoplastic polyurethane particles in the spinning precursor solution is 20wt%;

[0079] Electrospinning membrane: Add the prepared precursor spinning solution into the liquid storage mechanism of the electrospinning equipment, use the metal wire mesh 23 as the spinning collection mechanism of the electrospinning equipment, adjust the spinning parameters, and use the electrospinning equipment to directly electrospin the electrospun nanofiber membrane 24 on the upper surface of the metal wire mesh 23. The spinning parameters are as follows: a spinning distance of 15 cm, a spinning voltage of 45 kV, a spinning temperature of 25°C, a humidity of 20% RH, and a spinning time of 10 min.

[0080] Example 6 Heat Dissipation Experiment

[0081] The anti-haze window screens 2 of Examples 2-5 were cut into square samples of 10*10 cm, and the anti-haze window screens 2 samples of Examples 2-5 were placed at different positions on the surface of the copper plate, and the copper plate was placed on a heating table at 100°C. After 5 minutes, the surface temperature of the anti-haze window screens 2 samples was measured. The test results are shown in the following table:

[0082]

[0083] It can be seen from the above experimental results that the cordierite nanoparticles / thermoplastic polyurethane composite nanofiber membrane obtained by adding cordierite nanoparticles has a lower surface temperature than that of the pure thermoplastic polyurethane composite nanofiber membrane, that is, the cordierite nanoparticles / thermoplastic polyurethane composite nanofiber membrane has a better heat dissipation effect. Therefore, the use of the anti-smog screens for vehicles of Examples 2-5 can significantly improve the effect of heat exchange, quickly dissipate the heat in the car, and quickly reduce the temperature inside the car in the hot summer.

[0084] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A vehicle anti-smog screen window, characterized in that: It includes a screen window frame adapted to a vehicle window frame and an anti-smog window screen installed in the screen window frame, the screen window frame is provided with a connecting component for connecting to the vehicle window frame, the anti-smog window screen is a three-layer structure, which is sequentially arranged as a metal wire mesh, an electrospun nanofiber membrane and a plastic protective net, the electrospun nanofiber membrane is a cordierite nanoparticle / hydrophobic and oleophobic polymer material composite nanofiber membrane, the content of cordierite nanoparticles in the electrospun nanofiber membrane is 1-4wt%, the electrospun nanofiber membrane is directly sprayed and composited on the metal wire mesh by an electrostatic spinning method, the plastic protective net is fixed to the electrospun nanofiber membrane by ultrasonic welding, the ultrasonic welding has a plurality of welding lines and is staggered on the anti-smog window screen, and the plastic protective net is fixed to the electrospun nanofiber membrane by welding lines to form a plurality of dust bags.

2. The anti-smog screen window for vehicle according to claim 1, characterized in that: The dust bags are all rhombus-shaped with equal size, and the dust bags are evenly arranged on the anti-smog window screen.

3. The anti-smog screen window for vehicle according to claim 1, characterized in that: The metal wire mesh is a copper-plated stainless steel mesh, and the plastic protection mesh is a silver-plated nylon mesh; the mesh number of the metal wire mesh is 80-150 meshes, and the mesh number of the plastic protection mesh is 40-70 meshes. The porosity of the electrospun nanofiber membrane is greater than 80%, and the average pore size is 300-500nm.

4. The anti-smog screen window for vehicle according to claim 1, characterized in that: The connecting component is a magnet block attached to the screen window frame, and the magnet block is provided in plurality.

5. The anti-smog screen window for vehicle according to claim 1, characterized in that: The screen window frame is provided with a plurality of openings which can be used for folding the screen window frame.

6. The anti-smog screen window for vehicle according to claim 5, characterized in that: There are four openings, two of which are arranged along a vertical line passing through the midpoint of the bottom edge of the screen window frame, and the other two openings are arranged along a horizontal line passing through the midpoint of any side edge of the screen window frame.

7. The anti-smog screen window for vehicle according to claim 5, characterized in that: The screen window frame is provided with elastic buckles connecting the screen window frames at both sides of the opening, and the elastic buckles are arranged in one-to-one correspondence with the opening.

8. The anti-smog screen window for vehicle according to claim 1, characterized in that: The method for preparing the electrospun nanofiber membrane comprises the following steps: Preparing a spinning precursor solution: dispersing the cordierite nanoparticles in an organic solvent that can dissolve the hydrophobic and oleophobic polymer material to prepare a dispersion solution, adding the hydrophobic and oleophobic polymer material to the dispersion solution and mixing evenly to obtain a clear solution, which is a precursor spinning solution; Electrospinning membrane: Add the prepared precursor spinning solution into the liquid storage mechanism of the electrospinning equipment, use the metal wire mesh as the spinning collection mechanism of the electrospinning equipment, adjust the spinning parameters, and use the electrospinning equipment to directly electrospin the electrospun nanofiber membrane on the upper surface of the metal wire mesh.

9. The anti-smog screen window for vehicle according to claim 8, characterized in that: The electrospun nanofiber membrane is a cordierite nanoparticle / thermoplastic polyurethane composite nanofiber membrane; The step of preparing the spinning precursor solution is as follows: dispersing the cordierite nanoparticles in an organic solvent obtained by mixing N,N-dimethylformamide and tetrahydrofuran, treating with an ultrasonic crusher for 40-60 minutes, so that the cordierite nanoparticles are uniformly dispersed in the organic solvent to prepare a dispersion solution, wherein the volume ratio of N,N-dimethylformamide to tetrahydrofuran in the organic solvent is 1:1, adding thermoplastic polyurethane particles to the dispersion solution, heating in a water bath at 40° C. and stirring for 4-6 hours to obtain a clear solution, which is the precursor spinning solution; the content of the thermoplastic polyurethane particles in the spinning precursor solution is 20-25wt%, and the percentage of the cordierite nanoparticles to the total mass of the cordierite nanoparticles and the thermoplastic polyurethane particles is 1-4wt%; The spinning parameters in the electrospinning membrane making step are: spinning distance 15-25 cm, spinning voltage 45-60 kV, spinning temperature 25-30° C., humidity 20-40% RH, and spinning time 10-15 min.

10. The anti-smog screen window for vehicle according to claim 8, characterized in that: The preparation method of the cordierite nanoparticles comprises the following steps: Preparation of sol: According to the stoichiometric ratio of cordierite 2MgO·2Al2O3·5SiO2, weigh Mg(NO3)2·6H2O and Al(NO3)3·9H2O and dissolve them in anhydrous ethanol, heat and stir until completely dissolved, slowly drop a mixture of ethyl orthosilicate and anhydrous ethanol after cooling, wherein the volume ratio of ethyl orthosilicate to anhydrous ethanol in the mixture is 1:2, heat the obtained mixture to 52°C, stir and reflux, adjust the pH to 2.5 with nitric acid, and stir and react for 3 hours to form a sol; Gel preparation: Place the obtained sol in a 60°C water bath and let stand for 48 hours to form a gel; Sintering: The obtained gel is placed in a ceramic container, heated at 500°C for 10 hours, and then the obtained product is sintered at 1250°C for 2 hours to obtain cordierite powder; Crushing: The obtained cordierite powder is ball-milled to obtain cordierite nanoparticles, wherein the average particle size of the cordierite nanoparticles is 200 to 500 nm.

Citation Information

Patent Citations

  • Antifog haze screen window of formula car is inhaled to magnetism

    CN206562902U

  • Ceramic coating used for heating furnace

    CN102020475A

  • Magnetic sucking-type car anti-fog and anti-haze window screen

    CN106761342A

  • Anti-haze screen window and preparing method thereof

    CN107575151A

  • Anti-haze window screen based on electrospinning technology and preparation method thereof

    CN108071332A